Análisis jurídico doctrinario sobre el control de gastos 2 y 3 de la tabla de las pensiones alimenticias mínimas en procesos que se ventilan en el juzgado tercero adjunto de la familia niñez y adolescencia de El Oro, año 2013. - Espinoza Vijay, Jenniffer Lizbeth (2014)
This thesis aims to reform the Code Book II childhood and adolescence and enter unnumbered articles which allow the regulation of costs through mechanisms to monitor the 2 and 3 of the table minimum pension , whose purpose is to benefit the giving food a dignified life and that the legal representative not joys of income and / or resources for personal use , it is necessary to conduct a doctrinal law firm of several authors, the same found in the theoretical framework , taking aims to publicize the advantages and benefits of this new model of justice to ensure the right to decent life for children and sued for alimony, by conducting a critical analysis of the theoretical and conceptual foundations that underlie this job.